2009
DOI: 10.1093/toxsci/kfp275
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Rat Renal Organic Anion Transporters in Transporting Perfluorinated Carboxylates with Different Chain Lengths

Abstract: Perfluorinated carboxylates (PFCAs) are generally stable to metabolic and environmental degradation and have been found at low concentrations in environmental and biological samples. Renal clearance of PFCAs depends on chain length, species, and, in some cases, gender within species. While perfluoroheptanoate (C7) is almost completely eliminated renally in both male and female rats, renal clearance of perfluorooctanoate (C8) and perfluorononanoate (C9) is much higher in female rats. Perfluorodecanoate (C10) ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
147
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(152 citation statements)
references
References 50 publications
5
147
0
Order By: Relevance
“…Renal excretion of the longer chain PFCAs (!C10) is low in both genders (<5% [34]), and so movement into the renal filtrate may control renal excretion and serum half-lives. In the rat, OAT1 and OAT3 are both involved with the secretion of organic anions into the renal filtrate [28,32]; these transport proteins have a demonstrated affinity for the C7-C9 PFCAs [32]. Whether OAT1 or OAT3 can explain the longer serum half-lives in female rats as compared to male rats for PFDA [16] is not clear, because Kudo et al [28] did not observe any gender differences in their expression.…”
Section: Eliminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Renal excretion of the longer chain PFCAs (!C10) is low in both genders (<5% [34]), and so movement into the renal filtrate may control renal excretion and serum half-lives. In the rat, OAT1 and OAT3 are both involved with the secretion of organic anions into the renal filtrate [28,32]; these transport proteins have a demonstrated affinity for the C7-C9 PFCAs [32]. Whether OAT1 or OAT3 can explain the longer serum half-lives in female rats as compared to male rats for PFDA [16] is not clear, because Kudo et al [28] did not observe any gender differences in their expression.…”
Section: Eliminationmentioning
confidence: 99%
“…Oral absorption of organic anions is not well characterized, but likely involves organic anion transport (OAT) proteins [27]. The PFCAs and PFSAs have demonstrated affinity with a variety of OAT proteins [28][29][30][31][32], and this interaction has been implicated in gender and species differences observed in PFOA renal excretion [28,31]. Organic anion transport proteins are present in intestinal epithelial cells [27] as well as liver hepatocytes [33], both of which are involved in the movement of chemicals from the gut contents into the bloodstream.…”
Section: Oral Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The renal organic anion transporter system that mediates renal excretion and resorption [345] may differ depending on PFCA chain length, animal species and gender [212,346]. The immune response to PFOA and PFOS are also different: while the former reduced the number of B and T cells, the latter suppressed antigen specific antibody response independently from reduction in B and T cell numbers [224].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Studies on the elimination of PFOA by way of urine in rats showed a sex-dependent elimination effect. Vanden Heuvel et al (1991) reported that female rats eliminated 91 % of the intravenously administered dose by way of urine within 24 h. Due to the high excretion rate in female rats, the ability to express specific transporter systems in the kidney has been discussed (Weaver et al 2010). PFOS was excreted only in small proportions by way of urine and ranged near the LOD of 0.1 lg/L.…”
Section: Adsorption and Eliminationmentioning
confidence: 99%